English for religious purposes: An inquiry-based pedagogy for Muslim ESL learners - Preece, Abdul Shakour Duncan; Juperi, Juhasni Adila (IIUM Press, 2017)
This study explored ways of integrating Islamic content into ELT materials for the benefit of Muslim learners' language and faith. After analysing the literature, a sample of ELT materials was prepared to be used in conjunction with an inquiry-based pedagogy known as ‘Community of Inquiry’ (CI). This combination was termed ‘English for Religious purposes’ (ERP). ERP was then implemented over a period of five weeks with a group of adult Muslim learners studying ESL at a higher education institution in Kuala Lumpur. Qualitative research methodology was employed to gauge learners’ responses to ERP. The findings indicated that not only did ERP provide holistic practice in all four language skills in a meaningful and realistic way, but it also contributed to learners’ religious understanding and practice of Islam. This was put down to the engaging nature of whole-class inquiry-discourse characterised by CI. Moreover, the questions and issues introduced in the ERP texts stimulated students to express themselves and listen to the opinions of others with engagement. Participants reported benefits such as a desire to don the Muslim headscarf, performance of night prayers and the deepening of their faith. As such, ERP shows promise as a pedagogy for learners’ seeking to improve their English language and teachers wishing to deepen learners' understanding and practice of Islam.